On the Design of Sustainable and Fair PAYG Pension Systems When Cohort Sizes Change - Markus Knell (Oesterreichische Nationalbank (OeNB), 2005)
In this paper, the author deals with the question how to make PAYG pension systems financially resistant to fluctuating fertility rates. The author presents two pension schemes that lead to a permanently balanced budget but differ in the mixture of changes in the contribution rates and replacement rates they require in order to achieve this result. After analyzing the variations in the central parameters (both over time and across generations) for each of the schemes he discusses which consequences they have with regard to intergenerational burden sharing and fairness. In particular, the author is interested in how a generation is affected by changes in the size of proceeding and succeeding cohorts. He introduces a proportionality measure(defined as the ratio of relative inputs to relative outputs) that can be used as an indicator to study this impact. The author shows that the schemes have quite different implications concerning how past and future cohorts influence the proportionality measure. Finally he discusses how suitable the formulas are to be implemented in either traditional PAYG or in notional defined contribution (NDC) systems.
Keywords: H55; J1; J18; D63; 330; Pension System; Demographic Change; Intergenerational Fairness